Improvement of the ferroelectric properties of ABO(3) (A= Pb, Ca, Ba; B=Ti, Zr) films - Escote, M. T.; Pontes, F. M.; Mambrini, G. P.; Leite, E. R.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2005)
High-quality ABO(3)/LaNiO3 (A = Ph, Ca, Ba; B = Ti, Zr) hetero structures have been grown on LaAlO3 (1 0 0) substrate by the chemical solution deposition method and crystallized by a microwave oven technique. The structural, morphological and electric properties were characterized by means of X-ray diffraction (XRD), atomic force microscope (AFM), and dielectric and ferroelectric measurements. XRD patterns revealed single-phase polycrystalline and oriented thin films whose feature depends on the composition of the films. The AFM surface morphologies showed a smooth and crack-free surface with the average grain size ranging from 116 to 300 nm for both LaNiO3 electrode and the ferroelectric films. Dielectric measurements on these samples revealed dielectric constants as high as 1800 at frequency of 100 KHz. Such results showed that the combination of the chemical solution method with the microwave process provides a promising technique to grow high-quality thin films with good dielectric and ferroelectric properties. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: films; chemical solution deposition method; ferroelectric properties; perovskites; BaTiO3 and titanates